2004
DOI: 10.1021/jp0463363
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Relaxation Dynamics of Azide in Ionic and Nonionic Reverse Micelles

Abstract: Ultrafast infrared spectroscopy has been used to measure vibrational energy relaxation (VER) and reorientation times (T r) for the antisymmetric stretching band of azide ion (N3 -) in several reverse micelle (RM) systems using cationic, anionic, and nonionic surfactants. RMs were formed using H2O for all surfactants and D2O for the anionic and cationic surfactants. The vibrational dynamics depended on the RM charge. The charge dependence is attributed to differences in ion location in the RM because of Coulomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 74 publications
5
88
2
Order By: Relevance
“…The scattering intensity profiles of the AOT, iron, and methyl linolenate samples fit closely to the spherical form factor 14 suggesting that AOT formed monodispersed spherical reverse micelles upon addition to hexadecane, which is in agreement with earlier findings with AOT in various nonpolar solvents. [19][20][21][22] Multivalent transition metals such as iron and copper are effective lipid oxidation catalysts. Iron is found throughout nature and is commonly involved in biological oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering intensity profiles of the AOT, iron, and methyl linolenate samples fit closely to the spherical form factor 14 suggesting that AOT formed monodispersed spherical reverse micelles upon addition to hexadecane, which is in agreement with earlier findings with AOT in various nonpolar solvents. [19][20][21][22] Multivalent transition metals such as iron and copper are effective lipid oxidation catalysts. Iron is found throughout nature and is commonly involved in biological oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the possibility that the prooxidant activity of the iron could be decreased by dilution, a variety of studies 22,[34][35][36] have shown that the water inside reverse micelles differs from bulk water. Experimental and modeling studies 22,34,[36][37][38][39] suggest that there is a layered water pool structure where some water molecules are associated with surfactant head groups, some form an intermediate layer consisting of the next few nearest neighbors and, in the case of large reverse micelles, an interior region containing bulk water.…”
Section: Influence Of Ferrous Sulfate and Water On Lipid Oxidationmentioning
confidence: 99%
“…These studies, however, do not distinguish whether this slowing down holds for all of the water molecules present in RMs, or only for those present in the region of the surfactant head groups (interface). Recent studies employing techniques like vibrational echo and pump-probe spectroscopy, [4][5][6][7][8] absorption, [9][10][11][12][13][14] fluorescence, [3,[15][16][17][18][19][20][21][22][23][24][25][26] NMR, [27][28][29][30][31][32] calorimetry, [28,33] neutron scattering, [12,34,35] molecular dynamics simulation, [36][37][38][39][40] and so on have helped us in identifying different types of water in RMs, namely, water physically trapped between surfactant head groups, water directly bound (by HThe photophysical parameters of two probes with largely different hydrophobic character, namely, coumarin 1 and coumarin 343, are investigated in sodium bis-(2-ethylhexyl)sulfosuccinate (AOT)/hexane/water reverse micelles at various water/AOT molar ratio w 0 . Correlation of photophysical parameters such as fluorescence quantum yield, fluorescence lifetime, and emission maxima with w 0 indicate distinctly different trends below and above w 0 % 7 for both probes.…”
Section: O]/[aot]mentioning
confidence: 99%
“…The confinement of liquid water to small volumes changes its structure and dynamics [2][3][4][5][6][7][8][9][10][11][12][13] but also its phase behavior. Liquid water may be supercooled to much lower temperature when confined to micrometer sized capillaries.…”
Section: Introductionmentioning
confidence: 99%